ACCUMULATION OF HEAVY METALS IN CELERY PLANT APIUM GRAVEOLENS AND SOIL IRRIGATED WITH WASTEWATER WITHIN DUHOK CITY KURDISTAN OF IRAQ - Hussein, Zhina M.; Ahmed , Musher R. (Science Journal of University of Zakho, 2023)
Wastewater contains poisonous metals which can be moved and accumulated in plants before entering the human body through the food chain. The aim of this research was to investigate the concentrations of toxic metals such as Nickel (Ni), lead (Pb), and copper (Cu) in wastewater, celery plant and farmlands soils of Duhok city Kurdistan of, Iraq. The heavy metals accumulation in the Celery plants, soil and water samples were analyzed by using an atomic absorption spectrophotometer. The results obtained showed that the mean concentrations of Pb, Ni, and Cu in the wastewater and Celery plants samples ranged from 0.45±0.08 to 5.95±0.2, 0.18±0.01 to 1.95±0.28, 0.02± 0.01 to1.13±0.23 mg/L respectively. The pattern of metal buildup in wastewater-irrigated soil is in the order: Cu > Pb > Ni, and the mean concentration of Pb, Ni and Cu in soil ranged between 21.68±0.42 to 118.57±0.07, 1.27±0.47 to 5.70±0.23, 1.28±0.24 to ± 15.12 0.53 mg/kg-1, respectively. While the mean concentration of Pb, Ni and Cu in celery leaves ranged from 1.04±0.22 to 5.22±0.60, 0.52± 0.22 to 4.31± 0.12, respectively. 1.34 ±0.22 to 19.47±0.82, 1.23±0.04 to 7.29± 2.53, 1.01±0.05 to 5.76±1.32 mg/ kg-1, respectively. According to this study, roots contain more heavy metals than leaves. According to the findings, a few of the sampling sites had Pb, Ni, and Cu values that were exceeded the permissible concentration. Celery plants cannot be planted in the Duhok Valley to prevent excessive heavy metal exposure to human health through vegetables, where the main irrigated water source is sewage from the local municipalities. Celery plant irrigation with wastewater has much greater levels of heavy metals than the controls.